KEBIJAKAN PEMERINTAH KABUPATEN PEKALONGAN DALAM PENGELOLAAN LIMBAH BATIK (STUDI KASUS PENGELOLAAN AIR LIMBAH PADA INDUSTRI KECIL) - Andry Nurhidayat; Sulistyowati . (Journal of Politic and Government Studies, 2018)
The increasing number of small-scale batik industry players in Pekalongan district resulted in increasing of liquid waste of production which has an impact on the decrease of environmental quality. Waste water management policy is a strategic policy in order to realize sustainable environmental development as an effort to maintain water quality, as well as to improve the quality of waste water to prevent impacts that can damage the environment. This study aims are to determine the results of government policies on waste water management and to examine the participation and compliance of small batik industry actors against local regulation no. 5 year 2014. The researcher used mixed qualitative and quantitative research methods involving philosophical assumptions and mixing the research in one study. Data collection techniques are conducted through documentation, interviews, questionnaires and then the data are analyzed with mixed models of qualitative and quantitative analysis. The program carried out by the Government is said to be successful by seeing a reduction in the level of complaints from the public regarding pollution of industrial waste and an increase in environmental quality. However, what affects the less than optimal outcome of this policy is the low level of participation and adherence of small industry players seen from participation in decision making with poor criteria and participation in implementation with poor criteria. For the development of this policy, there is a need for decisiveness from the government in its supervision program of small batik industry players as well as adherence from small-scale batik industry players to Regional Regulation No. 5 of 2014 concerning Management of Wastewater.Keywords: Policy, Management, Participation, Obedience